1997
DOI: 10.1016/s0195-6701(97)90071-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for developing clinical infection with methicillin-resistant Staphylococcus aureus (MRSA) amongst hospital patients initially only colonized with MRSA

Abstract: In hospital outbreaks of methicillin-resistant Staphylococcus aureus (MRSA) many patients are initially colonized without infection. The reasons why some progress to infection while others do not are not known. A cohort of 479 hospital patients, initially only colonized with MRSA, was followed prospectively for the development of MRSA infection. Risk factors for progression to infection were assessed using Cox proportional hazards survival analysis. Fifty-three patients (11 .l%) developed 68 MRSA infections. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 14 publications
4
98
1
4
Order By: Relevance
“…Not surprisingly, these attributes are well known to be associated with a higher risk of HA-MRSA infection. [7][8][9]30 In addition, our study found that the proportion of admitted patients from lower socioeconomic backgrounds was also in-dependently predictive of a hospitals' proportion of HA-MRSA infections. The availability of resources in the home environment could influence the risk of HA infections that manifest in the immediate postdischarge period.…”
Section: Discussionmentioning
confidence: 49%
“…Not surprisingly, these attributes are well known to be associated with a higher risk of HA-MRSA infection. [7][8][9]30 In addition, our study found that the proportion of admitted patients from lower socioeconomic backgrounds was also in-dependently predictive of a hospitals' proportion of HA-MRSA infections. The availability of resources in the home environment could influence the risk of HA infections that manifest in the immediate postdischarge period.…”
Section: Discussionmentioning
confidence: 49%
“…[4][5][6][7] Patients who acquire MRSA incur significant risks of subsequent infection. [8][9][10] Importantly, MRSA carriage is associated with a fourfold increased infection risk compared with MSSA colonization. 11,12 Many studies have evaluated the risk factors for nosocomial MRSA acquisition (eg, comorbidities, exogenous factors, and antimicrobial exposure) to improve preventive measures, [13][14][15] but despite 50 years of research, less is known about the protective factors at the host level.…”
Section: Does Colonization With Methicillin-susceptiblementioning
confidence: 99%
“…This rate is comparable with rates reported elsewhere. 1,29 Older age, intensive care unit stay, receipt of hemodialysis, presence of surgical wounds, presence of pressure ulcers, and use of intravascular catheters have been associated with an increased progression of MRSA colonization to invasive infection. 1,29 ' 30 In our study, a higher number of risk factors at the end of follow-up was associated with an increased risk of MRSA infection.…”
Section: Mrsa Infection During Follow-upmentioning
confidence: 99%